2010
DOI: 10.1111/j.1540-8167.2009.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited Response to Cardiac Resynchronization Therapy in Patients with Concomitant Right Ventricular Dysfunction

Abstract: RVD represents a strong predictor of lack of clinical response to CRT in patients with CHF due to LVD and should be considered when prescribing CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
2
10
0
3
Order By: Relevance
“…Scuteri et al 19 have shown in a small group of patients that TAPSE is predictive of reverse LV remodelling following CRT. Among 130 CRT recipients, Tabereaux et al 20 recently demonstrated RV dysfunction to be an independent predictor of a heterogeneous composite adverse outcome including death, transplantation, need for LV assist device, lack of improvement in NYHA class and hospital care. Field et al 21 reported similar findings using RV myocardial performance as measurement of RV function.…”
Section: Discussionmentioning
confidence: 99%
“…Scuteri et al 19 have shown in a small group of patients that TAPSE is predictive of reverse LV remodelling following CRT. Among 130 CRT recipients, Tabereaux et al 20 recently demonstrated RV dysfunction to be an independent predictor of a heterogeneous composite adverse outcome including death, transplantation, need for LV assist device, lack of improvement in NYHA class and hospital care. Field et al 21 reported similar findings using RV myocardial performance as measurement of RV function.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of RV systolic function has been consistently associated with worse outcomes in patients with advanced heart failure, independently of LV function [20]. Previous studies reported that RV dysfunction represented a strong predictor of lack of clinical response to CRT [21][22][23]. In the present study, we used TAPSE, a simple, less dependent on optimal image quality and reproducible method to assess RV function and found that TAPSE was a strong variable to predict CRT response.…”
Section: Discussionmentioning
confidence: 99%
“…As patients develop progressive LV dysfunction, associated RV dysfunction also may develop. Evidence from recent studies suggests that RV dysfunction may be a further predictor of poor response to CRT [43]. Increased infarct size also may affect response, as it is known that patients with infarcted posterolateral walls have worse outcomes with CRT [44,45].…”
Section: Data Demonstrating Lack Of Response In Severe Cardiomyopathymentioning
confidence: 97%